Higher Dietary Inflammatory Index Scores Are Associated With Stress and Anxiety in Dormitory-Residing Female University Students in the United Arab Emirates - Attlee, Amita; Saravanan, Coumaravelou; Shivappa, Nitin; Wirth, Michael D.; Aljaberi, Mashael; Alkaabi, Reem; Bataineh, Mo'ath F.; Hebert, James R. (Frontiers in Nutrition, 2022)
Dormitory-residing university students are at-risk of mental health problems related to unhealthy diets. The purpose of this study was to assess the association between dietary inflammatory potential and mental health of dormitory-residing female university students. This cross-sectional study was comprised of 260 undergraduate females residing in dormitories of the largest university in United Arab Emirates during Spring 2019. Energy-adjusted Dietary Inflammatory Index (E-DIITM) scores computed from 37 food parameters were derived from two 24-hour dietary recalls. Logistic regression was used to estimate odds ratios (OR), and 95% confidence intervals (95% CI), for E-DII score in relation to depression, anxiety and stress. E-DII scores (mean= 2.98±1.17) were categorized into: tertile 1 (-1.96-2.62); tertile 2 (2.63-3.52); and tertile 3 (3.53-5.60), representing less to more pro-inflammatory diets. Students in E-DII tertile 3 had significantly higher depression, anxiety and stress scores. Logistic regression analysis showed that each point increase in E-DII score was associated with symptoms of stress (OR=1.41; 95% CI: 1.12-1.77; p=0.003) and anxiety (OR=1.35; 95% CI: 1.07-1.69; p=0.01). Relative to students in E-DII tertile 1 those in tertile 3 were more likely to be at higher risk of stress and anxiety; ORE-DIItertile3vs1=2.89 (1.44-5.79) and 2.88 (1.49-5.56), respectively. Overall, stress and anxiety were associated with pro-inflammatory diets in dormitory-residing female university students, suggesting the need for targeted interventions to increase the anti-inflammatory capacity of diet and improve mental well-being in students on university campuses.